Ion beam deflection in focusing magnetically insulated ion diodes with passive anode; Energy Fluxes and Radiation Effects (EFRE-2016) - Xiaopeng Zhu; Liang Ding; Qin Zhang; Pushkarev A. I. Aleksandr Ivanovich; Isakova Yu. I. Yulia Ivanovna; And Min Kai Lei (2016, 2016)
Title screen